Different Result Of Learner IPS Students Used Bowling Campus Active Learning Which Conventional Learning At SMPN 31 Padang Which Listed In 2013/2014 - Sumiran, Diana; Ramayani, Citra; Jolianis, Jolianis (Pendidikan Ekonomi, 2014)
ABSTRACTÂ This research based by low result of economy learner. That cause by some factors, the factors such as method which teacher still used teacher center. The goal of this research is for looking different result of learner students used Bowling campus active learning which conventional learning at SMPN 31 Padang. Kind of this result is experimental of research and interpretation sample technique that used is purposive sampling. Population of all the student grade VIII SMPN 31 Padang, wheares sample of this research are the students of VIII8 as experimental class and student of VIII7 as control class. Analysis data of technique which used SPSS software. Based analisys data the found is Ho regected an Ha accepted. So, that conclude there are different the result students learning used Bowling campus active learning with conventional learning. This result hoped can benefit for all are the leader for sosialization Bowling campus active learning especially teacher of economic and for researcher as reference for the next research.